Q-Der: a next-generation CoQ10 analogue supercharging neuroprotection by combating oxidative stress and enhancing mitochondrial function - Micucci, Matteo; Gianfanti, Federico; Donati Zeppa, Sabrina; Annibalini, Giosuè; Canonico, Barbara; Fanelli, Fabiana; Saltarelli, Roberta; Osman, Riham; Montanari, Mariele; Lopez, Daniele; Nasoni, Gemma; Panza, Giovanna; et al. (Frontiers in Molecular Biosciences, 2025)
BackgroundMitochondrial dysfunction and oxidative stress are central mechanisms in the progression of neurodegenerative diseases. This study first evaluated the toxicity of Q-Der (Q10-diacetate), a derivative of Coenzyme Q10, in HT22 hippocampal neurons under normal and oxidative stress conditions.MethodsHT22 cells were treated with Q-Der at 2.5, 5 and 10 µM with and without rotenone. Mitochondrial superoxide production (Mitosox), gene expression (via qRT-PCR), and protein levels (via Western blot) were measured. Morphological analyses were performed using transmission (TEM) and scanning (SEM) electron microscopes.ResultsQ-Der significantly reduced mitochondrial superoxide levels, particularly at 5 μM, and upregulated key mitochondrial biogenesis genes, including PGC-1α and TFAM. Additionally, it restored the expression of MT-ND1 and MT-COI, which were downregulated by rotenone. Western blot results showed a significant recovery in CV-ATP5A (complex V) expression (p < 0.05), preserving mitochondrial ATP production. Morphological analyses further confirmed Q-Der’s ability to maintain cellular and mitochondrial structure under stress conditions.ConclusionThese findings suggest that Q-Der is non-toxic under normal conditions and protects against oxidative stress, supporting its potential as a therapeutic agent for neurodegenerative diseases.